Challenge of extension agents against flood and natural disasters to develop agriculture sectors in Kelantan, Malaysia - Zaini, Nur Amirah (2016)
This study concerned the challenges of extension agents against flood and natural disasters to develop agriculture sectors in Kelantan, Malaysia. The study conducted in Kelantan which was affected by the massive floods in 2014 that recorded at most RM105 million in losses. Agricultural extension agent who are the intermediary between agencies and farmers play an important role in the development of agriculture in the affected areas. A questionnaire form was constructed in the Malay language as the main medium which contained 69 questions in several sections based on the objectives. The data were analysed using SPSS® for descriptive analysis and chi-square analysis. Socio-demographic profile of extension agents in Kelantan was established along with the current performance of the agents and their perception towards flood and natural disaster. The first objectives of this research project is to know the perception of extension agents toward flood and natural disaster, found that respondents’ has a high level of awareness toward the first objective. The second objective is to examine perception of respondents on knowledge, skill and practices toward post disaster farm management, which the respondents have a moderate level of knowledge, skill and practices on post disaster farm management. The third objective is to identify the challenges of extension agents on post natural disaster farm management, which also show moderate level of challenges. Lastly, to determine relationship between socio-demographic factor and respondent’s perception on knowledge, skill and practices toward post flood and natural disaster farm management. In the chi-square analysis, there was a relationship between age and the total annual income of respondent toward post flood and natural disaster farm management. To conclude, there is a room for improvement for better natural disaster farm management. To provide more training on climate change is highly recommended to government and private agencies for improvement. Besides, recruitement of new extension personnels from higher education institute will be a good way to implement latest technologies from high educational institutions.